Worship in ancient Israel : an essential guide - Brueggemann, Walter (Nashville, Tenn. : Abingdon Press, 2005)
"This guide describes the leading motifs of ancient Israel's worship traditions in the Old Testament. The author guides the reader through the themes, central texts, prayers, festivals, and practices of the worship. He sees throughout the Old Testament a central emphasis on worship as a convenantal gesture and utterance by the community in the presence of God. In addition to being an essential guide to this subject, this book is intended to be in the service of current theological and practical issues concerning worship of the church in its ecumenical character."--BOOK JACKET.
1. Orthodox Yahwism in dialogic modes -- 2. The gestures of worship and sacrifice -- 3. The utterance of YHWH in worship -- 4. The utterance of Israel in worship -- 5. Worship : Israel at "play"
Includes bibliographical references (p. 87-100) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Public worship in the Bible